Question prompt list responds to information needs of myelodysplastic syndromes patients and caregivers. Issue 6 (June 2015) - Mancini, Julien; Butow, Phyllis N.; Julian-Reynier, Claire; Dring, Rebecca; Festy, Patrick; Fenaux, Pierre; Vey, Norbert
Graphical abstract: Highlights: MDS patients and caregivers would have liked more information about prognosis (69.3%). Most participants endorsed a question prompt list (QPL) as absolutely useful (62.9%). The questions about prognosis were ranked among the first for usefulness. Interest in prognostic information was associated with interest in the QPL. Abstract: Myelodysplastic syndromes (MDS) are heterogeneous hematopoietic malignancies, often poorly understood by patients. Our aim was to obtain the views of MDS patients and family caregivers about a targeted question prompt list's (QPL) potential utility, and to evaluate their information needs. This targeted QPL, which included 53 suggested questions patients may ask onco-haematologists, was developed. A self-administered questionnaire eliciting feedback about the QPL and assessing its perceived usefulness was mailed to all members of Australian and French patients' national MDS associations. Respectively, 301 MDS patients and 53 caregivers responded. Most (76.4%) were satisfied with the information provided at MDS disclosure but would have liked more information about prognosis (69.3%). Consistently, the three most useful questions focused on the risk of leukaemic transformation, the impact of treatment on chances of survival and the severity of the MDS. The majority (62.9%) of both patients and caregivers perceived the QPL as ' absolutely ' useful, particularly those who would have preferred more information about prognosis (adjusted odds ratio = 2.3, 95% confidence interval [1.2–4.2], p = 0.008). Our proposal of intervention through a QPL was generally welcomed and could particularly address specific MDS patient needs regarding prognosis information.